Metabolic syndrome in children and adolescents with phenylketonuria - Viviane C. Kanufre; Rosângelis D.L. Soares; Michelle Rosa A. Alves; Marcos J.B. Aguiar; Ana Lúcia P. Starling; Rocksane C. Norton (Elsevier, 2015)
Objective: This study aimed to identify markers of metabolic syndrome (MS) in patients with phenylketonuria (PKU). Methods: This was a cross-sectional study consisting of 58 PKU patients (ages of 4-15 years): 29 patients with excess weight, and 29 with normal weight. The biochemical variables assessed were phenylalanine (phe), total cholesterol, HDL-c, triglycerides, glucose, and basal insulin. The patients had Homeostasis Model Assessment (HOMA) and waist circumference assessed. Results: No inter-group difference was found for phe. Overweight patients had higher levels of triglycerides, basal insulin, and HOMA, but lower concentrations of HDL-cholesterol, when compared to the eutrophic patients. Total cholesterol/HDL-c was significantly higher in the overweight group. A positive correlation between basal insulin level and HOMA with waist circumference was found only in the overweight group. Conclusion: The results of this study suggest that patients with PKU and excess weight are potentially vulnerable to the development of metabolic syndrome. Therefore, it is necessary to conduct clinical and laboratory monitoring, aiming to prevent metabolic changes, as well as excessive weight gain and its consequences, particularly cardiovascular risk. Resumo: Objetivo: Determinar marcadores bioquímicos da síndrome metabólica em pacientes com PKU. Métodos: Foram avaliados dois grupos de pacientes com PKU, 4 a 15 anos de idade, com excesso de peso (29) e eutróficos (29). As variáveis bioquímicas avaliadas foram a fenilalanina (phe), colesterol total, HDL-c, triglicérides, glicose e insulina basal. Foi determinado o HOMA e mensurada a circunferência da cintura. Resultados: As concentrações de phe, de colesterol total e de glicose foram equivalentes entre os grupos. Os pacientes com excesso de peso apresentaram maiores concentrações de triglicérides, de insulina basal, maiores valores da determinação do HOMA, menores concentrações de HDL colesterol e valores mais elevados da relação do colesterol total/HDL-c. Houve correlação positiva entre a dosagem de insulina basal e do HOMA com a circunferência da cintura nos pacientes do grupo com excesso de peso. Conclusões: Os resultados deste estudo sugerem que pacientes com PKU e excesso de peso são potencialmente vulneráveis ao desenvolvimento da síndrome metabólica. Há, portanto, necessidade de acompanhamento clínico-laboratorial que previna as alterações metabólicas, o ganho excessivo de peso e as suas consequências, em especial o risco cardiovascular. Keywords: Phenylketonuria, Metabolic syndrome, Children and adolescents, Overweight, Diet, Palavras-chave: Fenilcetonúria Síndrome metabólica, Crianças e adolescentes, Excesso de peso, Dieta